2003
DOI: 10.1177/153331750301800309
|View full text |Cite
|
Sign up to set email alerts
|

Creutzfeldt-Jakob disease: Two case studies

Abstract: Creutzfeldt-Jakob disease (CJD) is a rapidly progressive, neurodegenerative disorder causing dramatic neuromuscular symptoms, profound dementia, and death. In this article, the epidemiology, etiology, modes of transmission, clinical manifestations, determination of possible/probable CJD diagnosis in life, and the postmortem neuropathology of definite CJD are discussed in depth. Case studies of two individuals, each affected by different subtypes of sporadic Creutzfeldt-Jakob disease (sCJD), are presented, alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…These findings are consistent with previ v v ous studies showing fast motor decline in patients with sporadic CJD (21). Unlike other studies, we applied specific tests to evaluate daily loss, which showed fast, seve v v re impairment of motor, functional and cognitive v v capacities.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with previ v v ous studies showing fast motor decline in patients with sporadic CJD (21). Unlike other studies, we applied specific tests to evaluate daily loss, which showed fast, seve v v re impairment of motor, functional and cognitive v v capacities.…”
Section: Discussionsupporting
confidence: 89%
“…More controversially perhaps, they also raise the question of whether it is always right to inform the patient of their diagnosis. While Wickenden (2006) advises clinicians is to tell family the 'hard facts', such as CJD being a terminal condition, even though diagnosis uncertainty is emphasised, Rentz (2003), in an earlier paper, acknowledges that the communication of diagnosis may be distressing for all concerned.…”
Section: Families' Need For Supportmentioning
confidence: 99%